PENGARUH PENYULUHAN MENGGUNAKAN MEDIA VIDEO TENTANG STUNTING TERHADAP PENGETAHUAN, SIKAP DAN TINDAKAN IBU BALITA - Ria Astriani; Dedek Sutinbuk; Fitri Rizkiah (Masker Medika, 2023)
Introduction: Indonesia is still facing a double nutritional problem which has a serious impact on the quality of human resources (HR). One of the problems with malnutrition is that it is still quite high in Indonesia, especially the problem of stunting. The highest prevalence of stunting in 2022 is at the Sinar Baru Community Health Center at 1.6% compared to 3 Community Health Centers in the Sungailiat District working area, and this figure will still increase in 2023, namely stunting of 19 children (1.8%) and severe stunting of 2 children. (0.19%) even though health promotion efforts have been made by Puskesmas officers using lecture methods, distributing brochures and leaflets. Method: This research design uses a cross sectional study design. A sample of 101 mothers of toddlers was selected using purposive sampling. Data were analyzed by the Wilcoxon test. Results: There is an influence on the mother's knowledge before and after being given counseling using video media about stunting, namely p value (0.000) < 0.05, and there is an influence on the mother's attitude before and after being given counseling using video media about stunting, namely p value (0.000) < 0 .05 and there is an influence on the mother's actions before and after being given counseling using video media about stunting, namely p value (0.000) < 0.05. Discussion: Counseling using video media about stunting can increase the knowledge, attitudes and actions of mothers of toddlers in preventing stunting. Keywords: Knowledge, Attitude, Stunting, Video, Action